Mapping ecosystem services potential in Lithuania. Issue 5 (2nd September 2016) - Depellegrin, Daniel; Pereira, Paulo; Misiunė, Ieva; Egarter-Vigl, Lukas
ABSTRACT: This research presents a geographic information systems (GIS)-based method for ecosystem services (ES) potential assessment in a case study for the Lithuanian national territory. The ES potential was assessed for 31 CORINE land-cover classes (CLC2006) together with 31 ES categorized into regulating, provisioning and cultural ES. An expert-based ranking approach using a two-dimensional ES matrix and a geospatial analysis was applied to determine total ES potential, spatial patterns and relations among multiple ES. Results showed that forest areas had the highest potential for ES delivery whereas ES potential in urban areas was lowest. The spatial autocorrelation of regulating and cultural ES were dispersed while provisioning ES were significantly clustered. The principal component analysis (PCA) identified five factors with distinctive geospatial distribution: Factor 1 – forest areas, Factor 2 – aquatic environments, Factor 3 – livestock farming and energy production, Factor 4 – agricultural food production and Factor 5 – mineral extraction sites. The plotting of Factors 1 and 2 accounted for 72.81% of variance and identified three ES bundles composed by specific ES types: Bundle 1 – forest ecosystems, Bundle 2 – marine and freshwater ecosystems and Bundle 3 – mixed provisioning ecosystems. Trade-offs occur between regulating and cultural ES against the provisioning ES crop production and livestock farming. We conclude that the presented ES assessment can support decision-makers in the development of strategies for natural resources management at national and regional level, support the identification of trade-offs and synergies among ES types and foster ES research in Lithuania.